2020
DOI: 10.1371/journal.pone.0232442
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-derived exosome-like vesicles are enriched in lyso-phospholipids and pass the blood-brain barrier

Abstract: Exosomes are vesicles involved in intercellular communication. Their membrane structure and core content is largely dependent on the cell of origin. Exosomes have been investigated both for their biological roles and their possible use as disease biomarkers and drug carriers. These potential technological applications require the rigorous characterization of exosomal blood brain barrier permeability and a description of their lipid bilayer composition. To achieve these goals, we have established a 3D static bl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 52 publications
4
38
0
Order By: Relevance
“…EVs derived from biofluids such as plasma [ 124 ], and ascites [ 125 ], have shown potential as delivery carriers. Biofluid-derived EVs have several advantages as delivery carriers.…”
Section: How Crucial Is the Origin Of Exosomes For Drug Delivery?mentioning
confidence: 99%
See 2 more Smart Citations
“…EVs derived from biofluids such as plasma [ 124 ], and ascites [ 125 ], have shown potential as delivery carriers. Biofluid-derived EVs have several advantages as delivery carriers.…”
Section: How Crucial Is the Origin Of Exosomes For Drug Delivery?mentioning
confidence: 99%
“…For example, unlike cell culture-derived EVs, plasma-derived EVs are enriched with lyso-phospholipids and do not contain phosphatidylserine (PS). The absence of PS on the surface of plasma-derived EVs prevent their removal from circulation [ 124 , 126 ]. In addition, plasma-derived EVs can cross the blood-brain barrier (BBB), which suggests their applicability for brain delivery [ 124 ].…”
Section: How Crucial Is the Origin Of Exosomes For Drug Delivery?mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that EVs in peripheral blood can pass through the blood–brain barrier (BBB) [ 34 , 35 ]. Furthermore, it has been reported that neuron-derived EVs are taken up by endothelial cells and that the expression of endothelial cadherin is increased by miR132 contained in EVs [ 24 ], suggesting that neuronal EVs may be involved in the regulation of BBB integrity.…”
Section: Evs That Are Taken Up By Astrocytes Under Healthy Conditionsmentioning
confidence: 99%
“…Interaction between exosomes and BMECs in vitro shows that, in healthy and stroke-like conditions, exosomes retain their BBB crossing ability ( Chen et al, 2016 ). Exosomes crossed the BBB and were taken up by endothelial cells in a 3-D BBB static model ( Jakubec et al, 2020 ). This finding of exosome BBB crossing has been confirmed by a number of studies ( Grapp et al, 2013 ; Long et al, 2017 ; Yuan et al, 2017 ; Qu et al, 2018 ) however, biodistribution studies of exosomes reveal that, after intravenous administration of native exosomes to the body, they were rapidly cleaned from the target site and accumulated in organs of the reticuloendothelial system, such as the lungs, liver, and spleen, and very few exosomes were found at the target site ( Lai et al, 2014 ; Wiklander et al, 2015 ; Tian et al, 2018 ; Lu and Huang, 2020 ).…”
Section: Introductionmentioning
confidence: 99%